Lymphoepithelial carcinoma of the maxillary sinus: A case report (Indian Journal of Case Reports, 2022)
Lymphoepithelioma-like carcinoma or lymphoepithelial carcinoma (LEC) of the maxillary sinus is an extremely rare malignancy. It is a rare type of undifferentiated carcinoma, consisting of atypical epithelial cells surrounded by reactive lymphoplasmacytic infiltrate. The paper reports the case of a 76-year-old male patient, with complain of swelling on the hard palate and epistaxis. Biopsy from the hard palate mass showed features consistent with LEC, with contrast-enhanced computed tomography nasopharynx and neck showing soft-tissue lesion in the right maxillary sinus. The patient is currently under treatment with external beam radiotherapy.